Natural Product Chemistry for Drug Discovery - Buss, Antony D;Ed. Butler, Mark S;Ed (RSC biomolecular sciences, no. 18., 2010)
This up-to-date summary of natural product chemistry in drug discovery will appeal to scientists, professionals, postgraduates and industrial chemists.